2017
DOI: 10.12998/wjcc.v5.i12.412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori eradication on elder cases: Observational study in community-based medicine

Abstract: AIMTo examine the effect of Helicobacter pylori (H. pylori) eradication therapy on the extra-gastrointestinal factors in elderly patients by a before-after observational study in community medicine.METHODSMedical records (1 May 2013-31 January 2014) of 130 patients who underwent H. pylori eradication therapy with 2-year after-eradication observation in our institute were reviewed. Data on sex; age; body weight; body mass index (BMI); mean corpuscular volume (MCV); total protein; low-density lipoprotein cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…20 Several epidemiological studies focusing on the correlation between H. pylori colonization and BMI and obesity have shown contrasting results. 1,2,13,15,[21][22][23][24][25] A study from the Netherlands showed no evidence supporting a clinically relevant association between H. pylori and BMI/obesity, but a small negative association with obesity was present. 25 In a prospective randomized study of 1558 H. pylori-infected patients conducted in 2011, the BMI increased significantly after 6 months following randomization to H. pylori eradication therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…20 Several epidemiological studies focusing on the correlation between H. pylori colonization and BMI and obesity have shown contrasting results. 1,2,13,15,[21][22][23][24][25] A study from the Netherlands showed no evidence supporting a clinically relevant association between H. pylori and BMI/obesity, but a small negative association with obesity was present. 25 In a prospective randomized study of 1558 H. pylori-infected patients conducted in 2011, the BMI increased significantly after 6 months following randomization to H. pylori eradication therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is a definite need for a more focused analysis in the future, especially among patients showing sarcopenia or cachexia. Considering a Chinese study of elderly individuals, 15 HPE therapy could prevent further weight loss in those with sarcopenia or frailty. Among patients with the highest baseline BMI, the change in BMI after HPE was minimal (mean change [SD], We also performed stratified analyses for baseline age and sex and tested for the interaction effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, they reported a higher expression of sialic acid‐binding ( sab ) gene and vacuolating cytotoxin gene A ( vac A) in patients with IDA compared to healthy subjects . Maruyama et al clearly demonstrated how H. pylori eradication is able to decrease weight loss and prevent subclinical IDA in older subjects …”
Section: Hematologic Diseasesmentioning
confidence: 99%